Guiguinto horticulture resource center - Cabanatan, Angeline C.; Varona, Maria Faith Y. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
The Guiguinto Horticulture Resource Center is a facility that will be aiding Guiguinto's ornamental plant industry. Through research and development, using techniques in plant tissue culture and seed conservation, this building will house laboratories that will help produce new and improved species of plants, at the same time keeping a gene bank of all Guiguinto's ornamental plants. Through education, this facility hopes to be the resource center not only for the local seedling growers and sellers but to also anyone who wants to know more about the importance and benefits of planting. Through urban agriculture, this facility hopes to inspire the people to take the first step towards a self-sustaining future through exposure to new techniques. Being a municipality that prides itself being a garden city, this facility will be building among the people of Guiguinto a deeper appreciation and connection to the blooming greens that continues to grow around them.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman